Reducing lead time as a strategy for achieving optimal KPI performance at Kuehne Nagel BD. - Rahman, Afrina (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.